Web-based tools for product development. (30th March 2006) - Chang, C.M.
In the increasingly dynamic and challenging marketplace of the new millennium, many global companies must pursue operational excellence in order to make products and services better, cheaper and faster, and to gain and maintain short-term profitability. This paper discusses a number of web-based tools that may be advantageously applied to foster the companies' effectiveness in product development. Also presented are several factors deemed to be essential in product development, such as communications, information sharing, collaboration, design verification, configuration management and team management. The paper then elucidates the specific features of these tools, their vendors and the websites where additional information may be obtained. Furthermore, those industrial companies that applied these tools to derive benefits and the extent of these achievable benefits are also illustrated. Engineers are uniquely qualified to contribute to the product development efforts of many global companies. They play a vital role in helping their employers meet the product development challenges of the new millennium.